Studi Meta Analisis Problematika Evaluasi Program Bimbingan Konseling Di Sekolah - Zamratul Aini; Al Halik; Nurul Fajri (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2022)
this study aims to map various problems in implementing the evaluation of counseling guidance in Indonesia. This study uses a meta-analysis method, the first stage in the research is formulating the problem, and the second stage is the follow-up in the form of tracing the results of research with relevant titles for analysis. Search results of research through Google Scholar, Garuda portal, and repository, so that the sample in this study consists of 17 articles. The data analysis used in this research is described qualitatively. Research result. The results of the mapping of the implementation problems of the evaluation of counseling guidance can be concluded that the reasons behind the non-implementation of the evaluation of counseling guidance in schools are the first lack of understanding of BK teachers on the concept of evaluation of counseling guidance, the second background of BK officers is not from the counseling guidance study program, third there are still schools that do not plan the budget. for the implementation of the BK program, fourth there are still principals and BK personnel who do not play a role, fifth there is still a perception of a negative position from BK teachers regarding BK evaluation, fifth there is no provision of legal formats, and methods, sixth is the lack of training in the evaluation of counseling guidance in school